(untitled) (LACCEI, 2024)
At present, SMEs are a large part of the economic sector of Peru, and gradually the internal control of its employees has become a very important factor, because with a better accuracy of their daily record employees can be more efficient and generate favorable results against production, be paid with the corresponding payment of their extra activities so that the employee retribute to the company in the same way, so in this research will be mentioned about the attendance control of employees in companies. The objective of this research is to implement an artificial vision system with QR reader to control the attendance of employees in small and mediumsized companies. For the development of this system, we made use of different software such as Python version 3.10.7, Visual Studio Code and OpenCv, as well as specialized libraries such as PyQRCode, png, QRcode, numpy, among others for the coding of the three stages of the implemented system. Obtaining positive results in the total average efficiency of the project with 98.70%, indicating that this system of implementation proposed for the recognition in the attendance control of the collaborators of a company, can be executed effectively in any area.